Plant Secondary Metabolites on Efflux-Mediated Antibiotic Resistant Stenotrophomonas Maltophilia: Potential of Herbal-Derived Efflux Pump Inhibitors - Thi Huyen Thu Nguyen; Ngoc Anh Thơ Nguyen; Hai Dang Nguyen; Thi Thu Hien Nguyen; Mai Huong Le; Minh Quan Pham; Huu Nghi Do; Kim Chi Hoang; Serge Michalet; Marie-Geneviève; Hoang Nam Pham (MDPI AG, 2023)
During the process of adapting to metal contamination, plants produce secondary metabolites that have the potential to modulate multidrug-resistant (MDR) phenotypes; this is achieved by inhibiting the activity of efflux pumps to reduce the minimum inhibitory concentrations (MICs) of antimicrobial substrates. Our study evaluated the effect of secondary metabolites of belowground parts of Pteris vittata L. and Fallopia japonica, two metal-tolerant plants from northern Vietnam, on six antibiotic-resistant Stenotrophomonas maltophilia strains possessing efflux pump resistance mechanisms that were isolated from soil and clinical samples. The chemical composition of aqueous and dichloromethane (DCM) fractions extracted from P. vittata and F. japonica was determined using UHPLC-DAD-ESI/QTOF analysis. The antibacterial and efflux pump inhibitory activities of the four fractions were evaluated for the six strains (K279a, 0366, BurA1, BurE1, PierC1, and 502) using a microdilution assay at fraction concentrations of 62.5, 125, and 250 μg/mL. The DCM fraction of F. japonica exhibited remarkable antibacterial activity against strain 0366, with a MIC of 31.25 μg/mL. Furthermore, this fraction also significantly decreased gentamicin MIC: four-fold and eight-fold reductions for BurA1 and BurE1 strains, respectively (when tested at 250 μg/mL), and two-fold and eight-fold reductions for K279a and BurE1 strains, respectively (when tested at 125 μg/mL). Pure emodin, the main component identified in the DCM fraction of F. japonica, and sennidine A&B only reduced by half the MIC of gentamicin (when tested at 30 μg/mL). Our results suggest that the DCM fraction components of F. japonica underground parts may be potential candidates for new bacterial efflux pump inhibitors (EPIs).